Uobičajena iskustva i psihičke teškoće tokom pandemije: uvidi iz seansi psihološke podrške - Vukčević Marković, Maša; Šapić, Draga; Stanković , Biljana (Psihološka istraživanja, 2022)
Due to identified mental health difficulties among populations worldwide, evidence-based mental health and psychosocial support interventions are recognized as a priority for the health response to the COVID-19 pandemic. The main aim of this study was to provide in-depth understanding of the common experiences and psychological difficulties people with a COVID-19 diagnosis and their families and friends face. The study involved 32 persons (28 females), average age 38.53 (SD 13.24), that were infected with COVID-19, or whose family or friends were infected with COVID-19, receiving online psychological support from December 2020 to June 2021. Protocols of the support sessions were analyzed by relying on the principles of thematic analysis. The study results showed anxiety, somatization, sadness over the loss of close ones and guilt to be the most prominent psychological difficulties among people seeking psychological help during the pandemic. The main factors which made coping with psychological difficulties more challenging were previous life circumstances, uncertainty and lack of social support. The study enabled greater understanding of the common experiences and most prominent psychological difficulties, and provided evidence which can be used as a foundation for the creation of more focused psychological programs that could support people during the pandemic.